2006
DOI: 10.1111/j.1741-6248.2006.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Firm Performance: Further Evidence

Abstract: This article empirically investigates the competitiveness and stability of family‐owned firms relative to firms owned by diverse shareholders. Founding families are present in about one‐third of the S&P 500—the sample of this study. Data gathered over the 1992–2002 period confirm that family firms tend to experience higher employment and revenue growth over time and are more profitable. Regression analysis also supports that firm performance improves when founding family members are involved in management. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
315
5
41

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(385 citation statements)
references
References 27 publications
24
315
5
41
Order By: Relevance
“…Previous research on the relevance of firm size has shown that small firm size, as is prevalent in rural tourism, can block organisational development due to a lack of economies of scale, access to capital, bargaining power and employee attraction (Bamiatzi & Kirchmaier, 2014;Pansiri, 2007;Sundbo et al, 2007;Weiermair & Peters, 1998;Zhao & Getz, 2008). Larger (family) firms are also usually more able to endure financial crises (Lee, 2006) due to greater financial endowment. At the same time, small firms can benefit from more flexible business behaviour, such as being able to quickly react to environmental changes or by focusing on niche strategies (Bamiatzi & Kirchmaier, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Previous research on the relevance of firm size has shown that small firm size, as is prevalent in rural tourism, can block organisational development due to a lack of economies of scale, access to capital, bargaining power and employee attraction (Bamiatzi & Kirchmaier, 2014;Pansiri, 2007;Sundbo et al, 2007;Weiermair & Peters, 1998;Zhao & Getz, 2008). Larger (family) firms are also usually more able to endure financial crises (Lee, 2006) due to greater financial endowment. At the same time, small firms can benefit from more flexible business behaviour, such as being able to quickly react to environmental changes or by focusing on niche strategies (Bamiatzi & Kirchmaier, 2014).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The scale was adapted from the original dummy coding to fit the seven-point Likert scale generally applied within the questionnaire to ensure internal consistency. Financial Performance was measured by asking respondents to assess the extent to which their firm reached its performance targets over the previous three years on a seven-point Likert scale, ranging from 1 Bclearly underperformed^to 7 Bclearly exceeded^ (Lee 2006;Lindow et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…A clan is similar to a family-type organization and "typical characteristics of clan-type firms were teamwork, employee involvement and corporate commitment to employees" [18]. This clan feature of family firms has been confirmed by many researchers [19,20]. In family firms, commitment, harmony, long-term orientation and customer service are culture values generalized by Vallejo [21] and these values are consistent with the clan culture.…”
Section: Discussionmentioning
confidence: 57%